HUBUNGAN ANTARA KONFORMITAS TEMAN SEBAYA DITINJAU DARI JENIS KELAMIN DENGAN KEPATUHAN TERHADAP TATA TERTIB SEKOLAH - Hanna Permata Hanifa; Muslikah Muslikah (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2019)
Through a preliminary study with High School Counseling Teacher from High School 01 Jatisrono, Wonogiri, Central Java that obedience to school rules is still in the low category. On the other hand, students in their teens have the characteristics to conform with high peers. The purpose of this study was to determine the relationship between peer conformity in terms of gender with obedience to school rules. This research is a type of correlational quantitative research. Sampling using simple random sampling. The sample in this study amounted to 151 students spread throughout class XI. Measuring instruments used are the psychological scale of peer conformity and psychological scale of obedience to school rules. Analysis of the data used in the hypothesis test is the Carl Pearson product moment correlational test. The results showed that with the level of peer conformity in male and female students who were in the moderate category and found a positive and significant relationship between peer conformity in terms of gender with obedience to school rules with a low degree of correlation. Obtained correlation results of 0.261 with a significance of 0.001. From these results it can be understood that the higher the peer conformity, the higher obedience to school rules.